Analysis of Single Phase to Ground Faults Caused by Animals on Energy Not Served (ENS) in the Sumatera System - Januarsyah, Ginanjar; Widyanto, Aji Nur; Husnayain, Faiz (International Journal of Electrical, Computer, and Biomedical Engineering, 2025)
Animal disturbances on the High Voltage / Extra High Transmission Air Lines (SUTT / SUTET) in the work area of PT PLN (Persero) Sumatra Load Regulation and Distribution Center Main Unit (UIP3B Sumatra) during the period 2020-2024 have caused 208 animal disturbances on transmission lines and 35 animal disturbances on power transformers. This study provides information on mitigating animal interference, analyzing trends or patterns of animal habits that cause interference, and providing information on Energy Not Served (ENS). The data covers the period from 2020 to 2024, with a focus on evaluating the types of animals causing interference, the frequency and duration of outages, load data at the time of interference and the effectiveness of mitigation implemented, including recording the date, location, animal species, event classification, causal factors and response actions taken. This approach aims to improve understanding of the impact and behavior of wildlife on energy supply and to improve reliability and reduce the number of ENS.  The results showed that the behavior of each animal was consistent with the fault data analysis, and the largest amount of undelivered power was monkeys 629.15  MWh, followed by birds 391.167 MWh and 358.04 MWh. Reducing the number of disturbances is done by preventive maintenance in animal-prone areas, with regular monitoring and evaluation so that ENS can be minimized